2002
DOI: 10.1128/mmbr.66.4.592-616.2002
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Biodiversity: Approaches to Experimental Design and Hypothesis Testing in Primary Scientific Literature from 1975 to 1999

Abstract: Research interest in microbial biodiversity over the past 25 years has increased markedly as microbiologists have become interested in the significance of biodiversity for ecological processes and as the industrial, medical, and agricultural applications of this diversity have evolved. One major challenge for studies of microbial habitats is how to account for the diversity of extremely large and heterogeneous populations with samples that represent only a very small fraction of these populations. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 279 publications
1
65
0
7
Order By: Relevance
“…・Evaluate the taxonomic attribution of each tag in order to try to figure out the ecological role of each bacteria and the functioning of the community as a whole. Over time there has been numerous reviews of the methods available for studying microbial diversity 13,25,41,42,46,64,65,67,73,83,86,98,107,117,124,131,135,143,162,166,167,171,180,186) . Each method may have advantages and pitfalls, and there has been a tendency in recent years to simultaneously use several approaches, in order to obtain an extended view of the bacterial populations of complex ecosystems because some abundant species can be not retrieved by one of the methods 35,38,78,91) .…”
Section: Introductionmentioning
confidence: 99%
“…・Evaluate the taxonomic attribution of each tag in order to try to figure out the ecological role of each bacteria and the functioning of the community as a whole. Over time there has been numerous reviews of the methods available for studying microbial diversity 13,25,41,42,46,64,65,67,73,83,86,98,107,117,124,131,135,143,162,166,167,171,180,186) . Each method may have advantages and pitfalls, and there has been a tendency in recent years to simultaneously use several approaches, in order to obtain an extended view of the bacterial populations of complex ecosystems because some abundant species can be not retrieved by one of the methods 35,38,78,91) .…”
Section: Introductionmentioning
confidence: 99%
“…Hence our understanding of the significance of biodiversity for ecological processes in the microbial world or of the ways, in which we can manipulate or manage this diversity, is largely still unknown (Bull & Stach, 2004;Rosselló-Mora and Kämper, 2004;Tilman et al, 1997;Yachi & Loreau, 1999). Morris et al (2002) have largely attributed this failure or setback to problems associated with experimental designs and testing of hypothesis in ecological research. This notwithstanding, researchers have generally defined biological diversity at three levels of complexity:…”
Section: Microbial Diversitymentioning
confidence: 99%
“…Since alterations of the composition of the microbial community can be linked with functional changes in soil ecology, the soil bacterial community is an ideal indicator for the ecological status of soil and can thus help to evaluate how environmental and anthropogenic factors influence the soil ecosystem (Morris et al 2002). Although previous work has revealed that either chemical inputs (Kleineidam et al 2010) or plants (Berg and Smalla 2009) can affect soil microbial communities, few studies have evaluated the combined influence of agricultural chemical inputs and plant on bacterial community structure (Garcia-Teijeiro et al 2009, Doi et al 2011.…”
mentioning
confidence: 99%